A Puzzling Exam: Kernohan's Notch Reimaged. (October 2020) - Carlstrom, Lucas P.; Perry, Avital; Puffer, Ross C.; Graffeo, Christopher S.; Reuter, Peter J.; Fogelson, Jeremy L.; Wijdicks, Eelco F.
Highlights: We provide a visual image of the consequeces of massive brainstem shift with oculomotor and peduncle injury. Acute space occupying lesions may cause ipsilateral hemiparesis – and can be a false localizing sign.